The Effectiveness of Kumara Innovations in Improving the Quality of Public Services in the Department of Population and Civil Registration in Klungkung Regency - Gede Wirata; Ida Ayu Putu Sri Widnyana; I Made Sukarya Putra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine (1) the effectiveness of the implementation of the kumara innovation program in improving the quality of public services at the Department of Population and Civil Registration of Klungkung Regency and (2) what factors inhibit the effectiveness of the implementation of the kumara innovation program in improving the quality of public services at the Department of Population and Civil Registration. Klungkung Regency Civil Registration. This research method is descriptive research with a qualitative approach. Qualitative descriptive research is research that aims to describe and describe events and phenomena that occur in the field and present data in a systematic, factual, and accurate manner regarding facts or phenomena that occur in the field. Data were collected by using observation, interview, and documentation techniques. Researchers used source triangulation to check the validity of research data. Data analysis in this study uses three components consisting of data reduction, data presentation, and conclusion. The results of this study indicate that (1) the implementation of the Kumara innovation program has been effective in terms of service quality, and this innovation program has proven to be very helpful in making it easier for the community to get a child's identity card, this The innovation program has advantages in terms of the speed of the process of receiving a child's identity card. The results of this kumara innovation program have not been maximized in quantity, and the target of this kumara innovation program has not been achieved optimally, this is evidenced by the low percentage of ownership of identity cards for children who participate in the kumara innovation program services. (2) The factors that hinder the effectiveness of the implementation of the kumara innovation program at the Department of Population and Civil Registration of Klungkung Regency based on the results of the study are the lack of socialization, low public awareness, and budget constraints.